ANALISIS PENGENDALIAN PERSEDIAAN BARANG CONSUMABLE BERDASARKAN KLASIFIKASI ALWAYS BETTER CONTROL (ABC) DENGAN PENDEKATAN CONTINUOUS REVIEW DAN PERIODIC REVIEW PADA PT XYZ - Dinda Meimana (2023)
PT XYZ is a company engaged in the logistics industry that facilitates the ease of sending goods. In the past, inventory planning for consumable goods at PT XYZ has been based on estimates of past needs. Such methods have resulted in increased costs for the company due to overstocking or stockouts. Therefore, inventory management is needed to avoid stock shortages or excesses that could disrupt operational activities. The aim of this research is to analyze optimal inventory control planning for consumable goods that account for a significant portion of the company's expenses using the Always Better Control classification method, Single Moving Average, Weighted Moving Average, and Exponential Smoothing. Additionally, inventory control using the Continuous Review System and Periodic Review System will be examined. The ABC classification results indicate that only items categorized as A, specifically bags, account for nearly 80% of inventory expenses. Among the forecasting methods used, the Weighted Moving Average method demonstrates better accuracy with the smallest values for MAD, MSE, and MAPE. The research findings also show that the total inventory cost using the Continuous Review System is Rp 255.288.918, which is more optimal compared to the company's policy of Rp 312.881.811. Thus, the Continuous Review System method is considered optimal and can be implemented by the company, resulting in a reduction of inventory costs by 18.41%.